The effect of cobalt addition on structural and magnetic properties of electrodeposited iron-platinum nanocrystalline thin films - Teh, Sooh Hian; Yaacob, Iskandar Idris (Trans Tech Publications, 2010)
Iron-Platinum (Fe-Pt) and Cobalt-Iron-Platinum (Co-Fe-Pt) nanocrystalline thin films were deposited on brass substrates using a single bath electrodeposition system. The effects of addition of various concentrations of cobalt towards the composition, crystallographic structure, microstructure and magnetic properties of the Fe-Pt alloy films were investigated. Ammonium tartrate and ammonia solution were used as complex forming additives to stabilize the Fe2+ and Co2+ ions and to enhance co-deposition with platinum complexes. The as-synthesized thin films were characterized by energy dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD), scanning electron microscopy (SEM) and alternating gradient magnetometry (AGM). EDS results showed that cobalt was preferentially deposited compared to iron during Co-Fe-Pt film electrodeposition. SEM results showed that the microstructure of the films consisted of spherical granules. XRD showed formation of disordered face-centered cubic (fcc) Fe-Pt phase and all peaks were shifted to slightly higher diffraction angles with increasing cobalt content. The average crystallite size calculated from XRD peak broadening varied from 2.33nm to 6.54nm. The saturation magnetization and coercivity increased with increasing cobalt content. © (2010) Trans Tech Publications.